Historical occurrence of Antarctic icebergs within mercantile shipping routes and the exceptional events of the 1890s - Headland, Robert Keith; Hughes, Nicholas Edward; Wilkinson, Jeremy Paul (Journal of Glaciology, 2023)
A major consideration for maritime activity in the Southern Hemisphere is the northern limit of icebergs, or the Southern Ocean Limit Of Known Ice (SOLOKI). This analysis of historical reports of icebergs during Southern Hemisphere voyages from 1687 to 1933 provides a basis for examination of their geographical and chronological occurrence during ~250 years. The analyses use tabulated data from 742 voyages and other reports from many sources, some including first-person descriptions. While these data are dependent on icebergs being reported by mariners, as well as the variable frequency of voyages, they demonstrate distinct periods of exceptional frequency of icebergs occurring in certain localities, particularly the far South Atlantic. Based upon historical records the evidence suggests unprecedented numbers of icebergs were present in southern shipping channels in the 1890s. When these historical observations are combined with modern iceberg drift trajectories, their possible origin can be elucidated. Owing to the numbers of icebergs seen and their geographical spread, our results suggest that this was possibly the largest near-synchronous calvings in the last 300 years, and the northernmost extent of the SOLOKI.
Keywords: Sørishavet; glasiologi; isfjell

The Antarctic Peninsula: Argentina and Chile in the era of global change - Vidal, Florian (The Polar Journal, 2023)
While Argentine-Chilean relations have long been swayed between cooperation and confrontation since their independence in the 19th century and a long-standing presence in Antarctica, the stretch between Tierra del Fuego to the Antarctic Peninsula stands as the closest lane (i.e. about 1,000 km) to any other continent. Despite their territorial dispute over islands on the fractured southern tip of South America and territorial claims on the Antarctic, their common diplo-matic ground successfully defuses any potential geopolitical instability. Along with Chile and Argentina, British claims overlap in the Antarctic Peninsula, which establishes unique geopolitical conditions in the whole of Antarctica. In this context, scientific missions and growing tourist activities could transform the region into the Antarctic gateway. From potential mineral resources exploitation to the United States- China global competition, the South Atlantic area could become a strategic bridgehead in light of the brewing geopolitical shift during the 21st century. Considering that climate change and geostrategic conditions evolve somewhat quickly to transform the Western Antarctic area, this article aims to assess and comprehend how these external drivers may affect the two South American countries. Given the fact that Antarctica is part of their respective national narrative, how do Argentina and Chile intend to maintain their presence and protect their interest in these shifting conditions? What are the vectors for partnering with the world’s great powers, such as China? Ultimately, could this space become a choke point through the 21st century?
Keywords: Antarktis; geopolitikk; politikk; ressurser

Utryddelsen : historien om den norske industrielle hvalfangsten - Ytreberg, Espen (Press, 2023)
Det var det første norske oljeeventyret. I dag snakker ingen om det. I drøye hundre år etter at Svend Foyn oppfant granatharpunen i 1863, var Norge pådriver, innovatør og profitør i den største nedslaktingen av ville dyr verden noensinne har sett: Den globale industrielle hvalfangsten. Norge utviklet teknologi, åpnet nye fangstfelt og arbeidet internasjonalt for å hindre regulering og begrensninger. Da hvalfangstens epoke var over, var nesten ingen igjen av hvalene som hadde fylt verdenshavene. I dypet rådet en ny stillhet. Langs strendene i Sørishavet lå bare de råtnende hvalskrottene igjen. Men de norske hvalfangstrederne hadde blitt rike. Vanlige norske arbeidere bemannet den norske hvalfangstindustriens hvalkokerier og hvalbåter. For disse mennene var arbeidet slit, eventyr og mareritt. Etter dem finnes et stort materiale - fotografier, dagbøker, brev - som forteller om arbeidernes erfaringer fra slaktesonene i Sørishavet. I Utryddelsen forteller Espen Ytreberg historien om den norske hvalfangsten fra arbeidernes perspektiv. Han tar oss med på fangsten, lar oss følge arbeidernes opplevelser, setter bildene og beretningene deres inn i en større historisk sammenheng. Utryddelsen er et enestående stykke historieskriving om et avgjørende kapittel i norsk historie - en bok som åpner den nære norske fortiden opp for oss på helt nye måter.
Keywords: Sørishavet; hvalfangst